Evidências de arco magmático paleoproterozóico na região do Alto de Januária - norte de Minas Gerais - Christopher Rocha de Rezende (2017)
The studied rocks belong to the São Francisco Craton basement, nearly of Bonito de Minas (MG). They are exposed along dry creeks of the Januária High and are part of the homonymous complex. This work discusses, based on two papers, the petrographic, chemical and geochronological data of gneisses and granitoids of the Januária complex. The first paper classifies and identifies the geotectonic environments where these rocks were formed, based on petrography and geochemistry of these rocks. The second one outlines monazite chemistry and geochronological data, U-Th-Pb (non-isotopic), ages. The interpretation of the Paleoproterozoic tectonic cycle that affected the Januária Complex is based on the data of these two papers and the literature. During the Siderian, type I granitoids, calcic to calcic-alkaline, most of the high potassium, were formed in a continental magmatic arc environment (biotite granodiorite and biotite granites groups). At the same time, the process of metamorphism and anatexis of the pre-existing TTG crust would have begun. This process would reach its apex during the Rhyacian period in a collisional phase recorded in the gneisses of the region. During the Orosirian, with the orogen collapses, it would have been occured the biotite pink-granite intrusion. This biotite pink-granite, despite the similarities with type-A granitoids, was interpreted as post-collisional granite, formed in a high oxygen fugacity enviroment. Finally, in the Orosirian/Statherian limit, the anorogenic process related to the installation of the Espinhaço Rift is recorded by mafic dykes intrusions, related to the Januária swarm. The second paper reports the composition of five monazite crystals (A, B, C, D and E) from a migmatitic gneiss of granitic composition. These crystals were analyzed by electron microprobe and showed Ce-monazite composition, low percentages of cheralite and huttonite components and low deviations from the general chemical formula. According to the ages obtained by chemical method U-Th-Pb: monazite A presents average age of 2329 ± 55 Ma. This age data could be correlated to formation and intrusion of pre-collisional juvenile granitoids, contemporaneous to the beginning of the metamorphism and anatexis process of the pre-existing TTG rocks of Januária high. Monazite B has an average age of 2120 ± 56 Ma interpreted as being formed during the metamorphic peak and correlated to the sin-collisional phase of the Rhyacian period. The monazites C and D had mean ages of 1923 ± 28 and 1903 ± 29, respectively, indicating an orogen collapse. At last, the monazite crystal E outlines an average age of 1817 ± 37. Possibly, this age reports the anorogenic phase related to the formation of the Espinhaço rift. Acording these results, it is suggest that the Januária Complex would be a portion of the Rhyacian -Orosirian orogen in the central portion of the São Francisco Craton at Minas Gerais State.